2019
DOI: 10.1080/10408347.2019.1675043
|View full text |Cite
|
Sign up to set email alerts
|

Applications for Passive Sampling of Hydrophobic Organic Contaminants in Water—A Review

Abstract: We comprehensively review the current state-of-the-art of environmental monitoring for hydrophobic organic contaminants in aqueous matrices using passive sampling devices. Principles of the theory of passive sampling are presented. Strategies for passive sampler design and operation, limitations in performance and data quality-assurance and quality-control are reviewed. Advances in applications of available passive sampling devices are extensively critiqued. Future trends and current challenges facing practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 361 publications
(283 reference statements)
4
29
0
1
Order By: Relevance
“…The method developed here gives integrated sampling over time for the more frequently detected microorganisms, AllBac, NoV, and Vibrio spp., which is a characteristic of passive samplers in general (Taylor et al, 2019). These observations are consistent with our laboratory experiments in which we observed that the concentration of NoV on membranes increased with the duration of exposure (Vincent-Hubert et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…The method developed here gives integrated sampling over time for the more frequently detected microorganisms, AllBac, NoV, and Vibrio spp., which is a characteristic of passive samplers in general (Taylor et al, 2019). These observations are consistent with our laboratory experiments in which we observed that the concentration of NoV on membranes increased with the duration of exposure (Vincent-Hubert et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…A recent review of passive sampling of hydrophobic organic compounds [48] presents the monitoring principles for non-polar pesticides. At present, knowledge of the theory underpinning passive sampling of polar organic compounds, such as polar pesticides, is less developed.…”
Section: Passive Sampling Of Polar Pesticidesmentioning
confidence: 99%
“…In Figure 4, y-scale of Log C S /C M enabled researchers to observe the different accumulation trends of the active and passive samplers, and the black line at Log 10 indicates the equality of their concentrations. The upper part of the black line signifies that the metabolization of HOCs in the selected marine organism is higher, whereas the lower part of the black line indicates that the contaminants in the particular phase were higher than their dissolved forms, as a reminder that the dissolved phase of contaminants accumulated in the passive sampler (Bourgeault & Gourlay-Francé, 2013;Gourlay-Francé, Lor-geoux, & Tusseau-Vuillemin, 2008;Kim, Kim, Alvarez, Lee, & Oh, 2014;Lance et al, 2012;Luellen & Shea, 2002;Taylor, Fones, Vrana, & Mills, 2019;Zhao et al, 2018).…”
Section: Resultsmentioning
confidence: 99%